(Mis)Alignment of Challenges and Strategies in Promoting Inclusive Racial Climates in STEM Graduate Departments - Rosemary J. Perez; Rudisang Motshubi; Sarah L. Rodriguez (SAGE Publishing, 2023)
This descriptive qualitative study used racialized organizations (Ray, 2019) as a lens to examine how 27 faculty, administrators, and postdoctoral fellows in STEM departments at two institutions understood the problems that underlie negative racial climate, the strategies they used to improve racial climate, and the alignment between problems and solutions. Participants did not discuss racism and White supremacy as factors that contribute to negative racial climate. Instead, they indicated a weak STEM pipeline, and lack of faculty engagement created negative climate. Because participants did not attend to how racism and White supremacy fostered negative climate, their strategies (e.g., increased recruitment, committees, workshops) left systemic racism intact and (un)intentionally amplified labor for racially minoritized graduate students and faculty champions who often led change efforts with little support. These findings can help move departments away from intervention-centered models of change and toward more systemic approaches that contest how racialized organizations operate.